Operating system concepts. - Silberschatz, Abraham, ....-; Gagne, Greg, ....-; Galvin, P. B., ....- (Hoboken : Wiley, 2005)
Operating System Concepts 7/e, the best-selling introduction in the market, continues to provide a solid theoretical foundation for understanding operating systems. The seventh edition has been updated to offer coverage of the most current topics and applications, improved conceptual coverage and additional content to bridge the gap between concepts and actual implementations. The new two-color design allows for easier navigation and motivation. New exercises, lab projects and review questions help to further reinforce important concepts.